Duration of late-follicular elevated progesterone and in vitro fertilization outcomes in pituitary down-regulation treatment cycles - Zhang, Jiaxin; Ge, Xiaofei; Bu, Zhiqin (Frontiers in Endocrinology, 2023)
Background: The objective of this study was to explore whether the duration of LFEP (late-follicular elevated progesterone) affected pregnancy outcomes in IVF (in vitro fertilization) patients treated with pituitary down-regulation protocols. Method: Patients with their first IVF/ICSI cycles between January 2018 and December 2019 were included. LFEP was set either at P > 1.0ng/ml or P > 1.5ng/ml. Clinical pregnancy rate was compared among three different groups (no LFEP; LFEP for 1 day; LFEP for ≥ 2 days). Then multivariate logistic regression analysis was performed to explore the influencing factors of clinical pregnancy rate. Results: This retrospective analysis involved 3521 fresh embryo transfer cycles. Clinical pregnancy rate was the lowest in patients with LFEP duration ≥ 2 days, irrespective of LFEP was defined as P > 1.0 ng/ml (68.79% vs. 63.02% vs. 56.20%; P = 0.000), or was defined as P > 1.5 ng/ml (67.24% vs. 55.95% vs. 45.51%; P = 0.000). In addition, LFEP duration was significantly associated with clinical pregnancy outcomes in unadjusted logistic regression analysis. However, in multivariate regression models after adjusting confounders, adjusted OR for LFEP duration (≥ 2 days) in the two models was 0.808 (P = 0.064; LFEP as P > 1.0 ng/ml) , and 0.720 (P = 0.098; LFEP as P > 1.5 ng/ml), respectively. Conclusion: LFEP adversely affect clinical pregnancy outcomes. However, the duration of seems to have no influence on the clinical pregnancy rate in pituitary down-regulation treatment cycles.